2014
DOI: 10.3892/mco.2014.342
|View full text |Cite
|
Sign up to set email alerts
|

Lymph node spread of gallbladder cancer from the perspective of embryologically-based anatomy and significance of the lymphatic basin along the embryonic right hepatic artery

Abstract: Abstract. Lymph node metastasis from gallbladder cancer is often found in the pericholedochal area; however, these regional lymph nodes are not typically accompanied by arteries. We hypothesized that the artery accompanying pericholedochal lymph nodes was either the regressed embryonic right hepatic artery (eRHA) or an aberrant right hepatic artery (aRHA) remaining without regression. This study aimed to determine the artery supplying pericholedochal lymph nodes. We obtained serial tissue sections of resected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…Looking at the challenge imposed by the presence of aRHA during TMpE, namely that aRHA may be encountered during initial dissection of the SMA at the level of LRV, our study showed that the mean distance from the origin of SMA to the origin of aRHA (denoted by the green arrow in Figure 2A ) was 19.52 ± 3.87 mm, suggesting that dissecting the root of SMA at the level of LRV (denoted by the green line in Figure 2B ) is safe as this plane is posterior to the root and the course of aRHA. Furthermore, our study observed that the aRHA was related posteriorly to lymph nodes (Figure 3 ), this finding being compatible with the findings of Nakagawara and colleague’s manuscript [ 6 ]. These lymph nodes separate the aRHA from the dissection plane; however, they should be excised later as part of the standard lymphadenectomy during pancreatoduodenectomy.…”
Section: Discussionsupporting
confidence: 92%
“…Looking at the challenge imposed by the presence of aRHA during TMpE, namely that aRHA may be encountered during initial dissection of the SMA at the level of LRV, our study showed that the mean distance from the origin of SMA to the origin of aRHA (denoted by the green arrow in Figure 2A ) was 19.52 ± 3.87 mm, suggesting that dissecting the root of SMA at the level of LRV (denoted by the green line in Figure 2B ) is safe as this plane is posterior to the root and the course of aRHA. Furthermore, our study observed that the aRHA was related posteriorly to lymph nodes (Figure 3 ), this finding being compatible with the findings of Nakagawara and colleague’s manuscript [ 6 ]. These lymph nodes separate the aRHA from the dissection plane; however, they should be excised later as part of the standard lymphadenectomy during pancreatoduodenectomy.…”
Section: Discussionsupporting
confidence: 92%
“…They gave the reasoning that in en bloc resection procedure, it is difficult to determine the location of lymph node. 16,17 The meta-analysis by de Savornin Lohman et al evaluated the diagnostic accuracy of five studies and revealed uncertainty regarding the optimal imaging strategy for the preoperative detection of lymph nodal metastasis in carcinoma gallbladder. Routine imaging by CT is followed for preoperative staging.…”
Section: Discussionmentioning
confidence: 99%
“…They suggested that in cases with normal hepatic arterial branching, the lymphadenopathy observed was compatible with lymph nodes along a regressed embryonic right hepatic artery, and emphasized the importance of dissection along its course. 17 Lymphatic spread of gallbladder carcinoma occurs to lymph nodes around the cystic duct, common bile duct, and pancreaticoduodenal region. Carcinoma gallbladder spreads directly into the adjacent liver segments (IV and V), duodenum, colon, anterior abdominal wall, and common hepatic duct.…”
Section: Discussionmentioning
confidence: 99%